2020
DOI: 10.1021/acs.orglett.0c02714
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Mechanism of Photoaffinity Labeling by Dialkyldiazirines through Bioorthogonal Capture of Diazoalkanes

Abstract: Dialkyldiazirines have emerged as reagents of choice for biological photoaffinity labeling studies. The mechanism of crosslinking has dramatic consequences for biological applications where instantaneous labeling is desirable, as carbene insertions display different chemoselectivity and are much faster than competing mechanisms involving diazo or ylide intermediates. Here, deuterium labeling and diazo compound trapping experiments are employed to demonstrate that both carbene and diazo mechanisms operate in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…In contrast to the Ar tag and in agreement with previous reports, we have found that all the alkyl diazirine tags tested in this study are prone to intramolecular rearrangements to form unreactive side-products. 24 In the case of the DF-photoaffinity probe the formation of undesirable side-products may occur to such a degree no products of intramolecular reactions are detected in our decomposition experiments (Fig. S11 † ).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In contrast to the Ar tag and in agreement with previous reports, we have found that all the alkyl diazirine tags tested in this study are prone to intramolecular rearrangements to form unreactive side-products. 24 In the case of the DF-photoaffinity probe the formation of undesirable side-products may occur to such a degree no products of intramolecular reactions are detected in our decomposition experiments (Fig. S11 † ).…”
Section: Discussionmentioning
confidence: 77%
“…S8–S12 † ). 24 LC-MS peaks corresponding to intermolecular reaction (capture of solvent) were observed for all probes with the exception of DF–F.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Unlike -aryl and -heteroatom-stabilized diazo compounds, dialkyldiazo compounds are prone to protonation at the diazo substituted carbon; displacement of N 2 by a nucleophile can result in 'pseudo-carbene' photolabeling. 49,52,53 Because the intermediate diazo compound has a lifetime of milliseconds, 50 as compared to the picoseconds lifetime of the excited state carbene, this results in a broader labeling radius that is not diffusion limited.…”
Section: Synpacts Synlettmentioning
confidence: 99%